2020
DOI: 10.1016/j.asmr.2020.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Performance of PROMIS Physical Function, Pain Interference, and Depression Computer Adaptive Tests Instruments in Patients Undergoing Meniscal Surgery

Abstract: Purpose To compare the performance of the Patient-Reported Outcomes Measurement Information System (PROMIS) physical function (PF), pain interference (PIF), and depression computer adaptive tests (CAT) relative to legacy instruments in patients undergoing meniscal surgery. Methods Patients scheduled to undergo meniscal surgery completed legacy knee function PROMs (International Knee Documentation Committee [IKDC], Knee Injury and Osteoarthritis Outcome Score [KOOS] subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 55 publications
(72 reference statements)
0
13
0
Order By: Relevance
“…PROMIS CAT has been demonstrated to have strong responsiveness and minimal floor and ceiling effects in patients with knee pathology. 7,38 Thus, the use of PROMIS CAT forms as well as the findings of the present investigation can be beneficial in the shared decision-making process with patients who have suffered from ACL tears. For example, a moderately active 50-year-old female with an ACL tear who has pre-operative PROMIS CAT scores consistent with high physical function (PROMIS PF CAT >50.7) and low pain interference (PROMIS PI CAT <51.7) based on the calculated prognostic cutoffs may not receive a significant clinical benefit following ACLR and resultantly can be educated on alternative treatment options to surgical intervention.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…PROMIS CAT has been demonstrated to have strong responsiveness and minimal floor and ceiling effects in patients with knee pathology. 7,38 Thus, the use of PROMIS CAT forms as well as the findings of the present investigation can be beneficial in the shared decision-making process with patients who have suffered from ACL tears. For example, a moderately active 50-year-old female with an ACL tear who has pre-operative PROMIS CAT scores consistent with high physical function (PROMIS PF CAT >50.7) and low pain interference (PROMIS PI CAT <51.7) based on the calculated prognostic cutoffs may not receive a significant clinical benefit following ACLR and resultantly can be educated on alternative treatment options to surgical intervention.…”
Section: Discussionmentioning
confidence: 81%
“…3,4 In addition, PROMIS CAT health domains allow for a multifaceted evaluation of patient outcomes by interpreting pain interference (PROMIS PI CAT), physical function (PROMIS PF CAT), and depression (PROMIS D CAT) separately. 1,6,7 Recently, PROMIS CAT measures have demonstrated utility in measuring responsiveness to treatment following various orthopedic interventions. [8][9][10] However, postoperative statistical score improvements may not indicate clinical improvement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of studies reporting data on implementing clinic-based PRO measures and mobile applications for postoperative follow-up have enrolled young patients with an average age less than 60 years old 15 , 16 , 17 , 18 , 19 , 20 ; however, there is suggestion that older age may influence response times of patient reported outcomes. In a cross-sectional study of 3658 PROMIS forms administered in ambulatory clinics, Kadri et al.…”
Section: Discussionmentioning
confidence: 99%
“…for patients >49 years old. Patient age and sex did not significantly affect TTR or TTC for VAS, PROMIS-PI, or side-effect questions.A majority of studies reporting data on implementing clinic-based PRO measures and mobile applications for postoperative follow-up have enrolled young patients with an average age less than 60 years old[15][16][17][18][19][20] ; however, there is suggestion that older age may influence response times of patient reported outcomes. In a crosssectional study of 3658 PROMIS forms administered in ambulatory clinics, Kadri et al14 found that patients from the oldest age quartile (mean AE standard deviation, 70.3 AE 7.5 years) had a statistically significant longer TTC as compared with the second quartile (41.2 AE 4.7 years) (3.70 vs 2.87 minutes; P < .05).…”
mentioning
confidence: 99%